Chronic cerebrospinal venous insufficiency. Issue 6 (26th February 2013) - Barreto, Andrew D.; Brod, Staley A.; Bui, Thanh‐Tung; Jemelka, James R.; Kramer, Larry A.; Ton, Kelly; Cohen, Alan M.; Lindsey, John W.; Nelson, Flavia; Narayana, Ponnada A.; Wolinsky, Jerry S.
<x xml:space="preserve">Abstract</x> Objective Chronic cerebrospinal venous insufficiency (CCSVI) has been implicated in the pathophysiology of multiple sclerosis (MS). We sought to determine whether neurosonography (NS) provides reliable information on cerebral venous outflow patterns specific to MS. Methods This was a single‐center, prospective case–control study of volunteer MS and non‐MS participants. A neurosonologist, blind to the subjects' diagnosis, used high‐resolution B‐mode imaging with color and spectral Doppler to systematically investigate, capture, and record extracranial and intracranial venous drainage. These neuroimaging results were evaluated and scored by an expert blinded to subjects' information and with no interactions with the participants. Results Altogether, 276 subjects were studied: 206 with MS and 70 non‐MS. MS patients were older than non‐MS subjects (48.3±9.9 vs 44.3±11.8 years, p<0.007), with durations from first symptoms and diagnosis of 13.7±10 and 9.9±7.8 years, and Expanded Disability Status Scale of 2.6±2.0. Overall, 82 subjects (29.7%) fulfilled 1 of 5 NS criteria proposed for CCSVI; 13 (4.7%) fulfilled 2 criteria required for diagnosis, and none fulfilled >2 criteria. The distribution of subjects with 0, 1, or 2 criteria did not differ significantly across all diagnostic groupings, between MS and non‐MS subjects, or within MS subgroups. CCSVI was present in 7.14% of non‐MS and 3.88% of MS patients (p=0.266). No significant differences emerged between MS and non‐MS subjects for extracranial or intracranial venous flow rates. Interpretation NS findings described as CCSVI are much less prevalent than initially reported, and do not distinguish MS from other subjects. Our findings do not support the hypothesis that CCSVI is causally associated with MS. ANN NEUROL 2013;73:721–728